2017
DOI: 10.7554/elife.22796
|View full text |Cite
|
Sign up to set email alerts
|

Patterned cortical tension mediated by N-cadherin controls cell geometric order in the Drosophila eye

Abstract: Adhesion molecules hold cells together but also couple cell membranes to a contractile actomyosin network, which limits the expansion of cell contacts. Despite their fundamental role in tissue morphogenesis and tissue homeostasis, how adhesion molecules control cell shapes and cell patterns in tissues remains unclear. Here we address this question in vivo using the Drosophila eye. We show that cone cell shapes depend little on adhesion bonds and mostly on contractile forces. However, N-cadherin has an indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 84 publications
8
68
0
1
Order By: Relevance
“…We computed the averaged opening dynamics following laser cuts for each type of junctions, and extracted the corresponding initial recoil velocity ( Figure 3C, 3D). As previously demonstrated (Chan et al 2017), this revealed a gradation of tensions according to junction type. Homotypic EN|EN junctions have the lowest tensions, E|E junctions have intermediate tensions, and heterotypic EN|E junctions have the highest tensions ( Figure 3F).…”
Section: -Stereotyped Tension Patterns In Wild Type and Mutant Ommatidiasupporting
confidence: 78%
See 4 more Smart Citations
“…We computed the averaged opening dynamics following laser cuts for each type of junctions, and extracted the corresponding initial recoil velocity ( Figure 3C, 3D). As previously demonstrated (Chan et al 2017), this revealed a gradation of tensions according to junction type. Homotypic EN|EN junctions have the lowest tensions, E|E junctions have intermediate tensions, and heterotypic EN|E junctions have the highest tensions ( Figure 3F).…”
Section: -Stereotyped Tension Patterns In Wild Type and Mutant Ommatidiasupporting
confidence: 78%
“…To achieve this, we turned to the retina of Drosophila, composed of highly stereotyped groups of cells called ommatidia ( Figure 3A). Previous studies showed that cone cell shapes and arrangements in ommatidia are determined by differential tensions (Hayashi & Carthew 2004;Käfer et al 2007;Hilgenfeldt et al 2008;Chan et al 2017). These tensions were shown to be determined by the amounts of Myo-II and E-and N-cadherins recruited at the considered junctions (Chan et al 2017).…”
Section: -Stereotyped Tension Patterns In Wild Type and Mutant Ommatidiamentioning
confidence: 99%
See 3 more Smart Citations